Expression of the pacemaker channel HCN4 in excitatory interneurons in the dorsal horn of the murine spinal cord - Nakagawa, Taku (Mol Brain, 2020)
In the central nervous system, hyperpolarization-activated, cyclic nucleotide-gated (HCN1–4) channels have been implicated in neuronal excitability and synaptic transmission. It has been reported that HCN channels are expressed in the spinal cord, but knowledge about their physiological roles, as well as their distribution profiles, appear to be limited. We generated a transgenic mouse in which the expression of HCN4 can be reversibly knocked down using a genetic tetracycline-dependent switch and conducted genetically validated immunohistochemistry for HCN4. We found that the somata of HCN4-immunoreactive (IR) cells were largely restricted to the ventral part of the inner lamina II and lamina III. Many of these cells were either parvalbumin- or protein kinase Cγ (PKCγ)-IR. By using two different mouse strains in which reporters are expressed only in inhibitory neurons, we determined that the vast majority of HCN4-IR cells were excitatory neurons. Mechanical and thermal noxious stimulation did not induce c-Fos expression in HCN4-IR cells. PKCγ-neurons in this area are known to play a pivotal role in the polysynaptic pathway between tactile afferents and nociceptive projection cells that contributes to tactile allodynia. Therefore, pharmacological and/or genetic manipulations of HCN4-expressing neurons may provide a novel therapeutic strategy for the pain relief of tactile allodynia.